2017
DOI: 10.1590/0102-6720201700040011
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Diagnosis and Operative Management

Abstract: Introduction: Hepatocellular carcinoma is an aggressive malignant tumor with high lethality. Aim: To review diagnosis and management of hepatocellular carcinoma. Methods: Literature review using web databases Medline/PubMed. Results: Hepatocellular carcinoma is a common complication of hepatic cirrhosis. Chronic viral hepatitis B and C also constitute as risk factors for its development. In patients with cirrhosis, hepatocelular carcinoma usually rises upon malignant transformation of a dysplastic regenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 31 publications
0
54
0
7
Order By: Relevance
“…The results indicated that NCAPH expression was significantly increased in these datasets (Figure A‐F). The qRT‐PCR results showed that NCAPH expression was significantly higher in HCC tissues than in normal tissues (G). In addition, the IHC results demonstrated that the NCAPH immunostaining signals were stronger in HCC tissues than in adjacent normal liver tissues (ANLTs; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that NCAPH expression was significantly increased in these datasets (Figure A‐F). The qRT‐PCR results showed that NCAPH expression was significantly higher in HCC tissues than in normal tissues (G). In addition, the IHC results demonstrated that the NCAPH immunostaining signals were stronger in HCC tissues than in adjacent normal liver tissues (ANLTs; Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), as one of the most common cancers, is the leading cause of cancer-associated deaths in China with a characteristic of high morbidity and mortality [1][2][3]. One sorrowful fact about HCC is that the number of HCC patients has been increasing annually.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, 900 patients received surgical treatment for HCC. However, this trial demonstrated that there is no statistical difference in survival between the group of patients receiving sorafenib and the control group [5].…”
mentioning
confidence: 76%
“…Alcohol is also a factor associated with predisposition to liver cirrhosis and, consequently, to HCC, as 80%-90% of patients with HCC have cirrhosis regardless of this etiology [4]. In the United States, alcohol consumption is a relevant risk factor, since the country reports alcohol abuse as a cause related to the development of the disease five times more than hepatitis C [3,5].…”
mentioning
confidence: 99%